Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.3109/10408449009089868
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Critical Levels of Toxic Heavy Metals in Target Tissues

Abstract: The high reactivity of heavy metals with biological systems is well documented, although some disagreement remains on the precise dose-effect relationships involved. This represents a question of considerable importance, especially in attempts to assess the risks of exposure. The implicit assumption is usually made that a threshold concentration of specific metals exists in the most sensitive target organ, so that an increased frequency of functional lesions will be expected if this threshold is exceeded. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The present study examines Cu-Cd interactions in mature tilapia, paying particular attention to organs with diverse biological functions, because it is anticipated that differences in metal accumulation between organs will be related to their functions. Organ metal concentration or metalmetal interaction at this level may be a link to toxicity (Foulkes, 1990;Landrum et al, 1992). In keeping with this, it has recently been suggested that metal concentrations in the organs of fish, rather than the metal concentrations in the ambient water, could be used as a biomonitor for water pollution in natural freshwaters (Handy, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The present study examines Cu-Cd interactions in mature tilapia, paying particular attention to organs with diverse biological functions, because it is anticipated that differences in metal accumulation between organs will be related to their functions. Organ metal concentration or metalmetal interaction at this level may be a link to toxicity (Foulkes, 1990;Landrum et al, 1992). In keeping with this, it has recently been suggested that metal concentrations in the organs of fish, rather than the metal concentrations in the ambient water, could be used as a biomonitor for water pollution in natural freshwaters (Handy, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The critical concentration of cadmium in the renal cortex below which no adverse effect would be anticipated has been estimated at about 200 pg/gram fresh weight (Foulkes, 1990;EPA, 1994a …”
Section: Joxicitv Of Ca Dmiummentioning
confidence: 99%
“…Progressive disruption of kidney function will lead to an increase in amino acids, glucose, phosphate, and protein in the urine. The critical concentration of cadmium in the renal cortex below which no adverse effect would be anticipated has been estimated a t about 200 pg/gram fresh weight (Foulkes, 1990;EPA, 1994a). However, the apparent critical level of cadmium in the kidney can vary substantially under different conditions of exposure; it can be affected by age, sex, and other factors influencing individual sensitivity to cadmium toxicity.…”
Section: Toxicitv Of Cadm Iummentioning
confidence: 99%